Surgical aspects of interest in the pathology of Gastric Carcinoma - Vercelli Retta, J (Cirugía del Uruguay, 1988)
Despite the progress of treatment, patients carriers of gastric carcinomas (GC) advanced still have a poor prognosis, with a overall survival of approximately 5% after 5 years after diagnosis. These concepts refer to advanced GC, that is, lesions that have infiltrated the muscular layer of the organ itself.